Self-Compassion Tendencies of West Javanese Students and Their Implications for Culture-Based Humanistic Counseling - Riesa Rismawati Siddik; Williya Novianti; Dona Fitri Annisa (Journal of Education and Counseling (JECO), 2026)
This study investigated the level of self-compassion among university students in West Java and explored its implications for culture-based humanistic counseling. A descriptive quantitative approach was employed involving 569 university students from various higher education institutions in West Java. Data were collected using an adapted Self-Compassion Scale based on Neff's six dimensions: self-kindness, self-judgment, common humanity, isolation, mindfulness, and over-identification. Descriptive statistical analysis was used to determine the distribution of students' self-compassion levels and the tendency of each dimension. The findings revealed that 66.26% of students were categorized as having moderate self-compassion, 17.57% were in the low category, and 16.17% were in the high category. Aspect-based analysis showed that self-kindness and common humanity represented the strongest dimensions, indicating that students generally possessed the ability to understand personal difficulties and recognize them as part of shared human experiences. In contrast, self-judgment, mindfulness, and over-identification were relatively less developed, suggesting that many students still experienced excessive self-criticism and difficulties regulating negative emotions. Overall, the findings indicate that students possess a foundation for emotional resilience, although support is still needed to strengthen adaptive emotion regulation and reduce maladaptive self-evaluation. These findings suggest that culture-based humanistic counseling integrated with local values has the potential to enhance self-compassion among university students.